Leben aus dem Geiste oder: Warum Bildungseinrichtungen als menschliche Entfaltung tragende ‚Gemeinden’ gedacht werden sollten - Girmes, Renate (International Dialogues on Education Journal, 2017)
The following text explores existing arguments for a new view on the tasks of the education system from a tradition of Christian thought. It takes up what can be considered the sense and promise of baptism in its argument for the endorsement of the Gospel of John in this tradition. A way of reading in this tradition is also developed, revealing what foundational information on the nature of intergenerational relationships can be found in the biblical text, and what connected challenges a professional education and learning praxis faces.